Study guides

☆☆

Q: -5b - 12 -2 what is b?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

Not sure how the problem is set up as I see a space between the minus sign and the 12 but not between the minus and the 2. But, using the numbers as written: To solve for b, you must form an equation (-5b -12 -2 = 0). Next you must separate the known numbers from the unknown by adding the sum of the knowns to both sides of the equation (-5b = 14). Then divide both sides of the equation by -5 to find the value of b (b = -2.8). No no no no no. It is -5b-14 because the -5b has no relation to the others so it stays as it is and then -12-2=-14 thus getting -5b-12-2=-5b-14. Cool.

-b+5b-2b=2b

8b + 11 - 3b = 2b + 2 5b + 11 = 2b + 2 5b - 2b = 2 - 11 3b = -9 b = -3

5b2 = 8b therefore 5b =8 therefore b = 1.6

No. 7b - 2b = 5b

Related questions

Not sure how the problem is set up as I see a space between the minus sign and the 12 but not between the minus and the 2. But, using the numbers as written: To solve for b, you must form an equation (-5b -12 -2 = 0). Next you must separate the known numbers from the unknown by adding the sum of the knowns to both sides of the equation (-5b = 14). Then divide both sides of the equation by -5 to find the value of b (b = -2.8). No no no no no. It is -5b-14 because the -5b has no relation to the others so it stays as it is and then -12-2=-14 thus getting -5b-12-2=-5b-14. Cool.

12 and 60 ============ a + b = 72 a = 5b replacing a by 5b in the first equation 5b + b = 72 6b = 72 b = 12 72 - 12 = 60

5b + 21b = 1226b = 1226 26b = 12/26

5ab-2ab+4a-b+5b = 3ab+4a+4b

(1) 4a-5b=7 (2) 4a+5b=17 (1)-(2) gives 4a-5b-(4a+5b)=7-17 then -10b=-10 so b=1 from (2) one gets 4a=17-5b=17-5x1=12 so a=3 (3,1) is the solution

If: 5b = 30 Then: b = 6

-b+5b-2b=2b

5b + 5b = 2 x 5b

-5a + b = 2 AND -a - 5b = 0 -5a + b = 2 b = 2 + 5a *using above -a - 5b = 0 -a - 5(2 + 5a) = 0 -a - 10 - 25a = 0 -26a = 10 a = 10/-26 *using 'a' value 5a + b = 2 5(10/-26) + b = 2 -25/13 -2 = -b b = 51/13 Therefore a = 10/-26 b = 51/13

10a - 5b = 25 So 5b = 10a - 25 and hence b = 2a - 5

10a + 5b

6(b + 2)(5b - 2)

People also asked